You can't go wrong doing right : how a child of poverty rose to the White House and helped change the world - Brown, Robert J., 1935- (Convergent, 2019)
"An unforgettable account of a quietly remarkable life, Robert Brown's memoir takes readers behind the scenes of pivotal moments from the 20th century, where the lessons he learned at his grandmother's knee helped him shape America as we know it today." -- Publisher annotation.